Pengaruh Penerapan Pembelajaran Berdiferensiasi terhadap Minat dan Hasil Belajar Peserta Didik pada Mata Pelajaran Bahasa Indonesia - Muhajiroh, Ellya; Fauzi, Ahmad; Imron, Ali (Universitas Islam Tribakti Lirboyo Kediri, 2025)
This study aims to analyze the effect of implementing differentiated learning on students' interest and learning outcomes in the Indonesian language subject at SD Negeri Sidomulyo 1, Puncu District, Kediri Regency. The differentiated learning approach is used to adjust the content, process, and product of learning based on students’ readiness, interests, and learning profiles. This research employs a quantitative method with an experimental design, in which data were collected through pretests, posttests, and observations during the learning implementation. The results show that the implementation of differentiated learning has a significant effect on increasing students’ interest and learning outcomes in the Indonesian language subject at SD Negeri Sidomulyo 1, Puncu District, Kediri Regency. Based on the paired sample t-test, there is a significant difference between pretest and posttest scores after the application of differentiated learning, both in terms of learning interest and outcomes. Moreover, the Pearson correlation test results indicate a significant positive relationship between learning interest and students’ learning outcomes. This study concludes that differentiated learning positively impacts students’ interest and learning outcomes while supporting the implementation of the Kurikulum Merdeka, which emphasizes an inclusive and adaptive approach. These findings contribute to the development of a learning model that is responsive to student diversity and relevant to improving the quality of education at the elementary level.